Faktor - faktor yang mempengaruhi nilai produksi usahatani tanaman pakcoy dengan sistem hidroponik di Kota Jambi - Yuliani, Rahmi; Hardiani, Hardiani; Hari Prihanto, Purwaka (e-Journal Perdagangan Industri dan Moneter, 2023)
This research aims 1) to analyze the socio-economic characteristics of hydroponic farming in Jambi City and 2) to analyze the influence of capital, land area and labor on the production value of hydroponic farming in Jambi City. The analytical tool used in this research is multiple linear regression. The results of this research show that based on the characteristics of hydroponic farming in Jambi City, it can be concluded that the average capital for hydroponic farming is IDR. 1,413,158, the average land area owned is 143M2, the average workforce is only 1 person, the average production of hydroponic vegetables produced is 84 kg and the average production value is hydroponic amounting to Rp. 1,004,632 per week. Based on the results of simultaneous tests, capital, land area and labor together have a significant effect on the production value of hydroponic farming in Jambi City. Then, based on the t test, it shows that capital and land area have a significant effect on the production value of hydroponic farming in Jambi City. While the labor variable has no effect on the production value of hydroponic farming, it is not significant on the production value of hydroponic farming in Jambi City. The knowledge Rsquare value is 0.984, meaning that 98.4 percent of the variation in hydroponic production of pokcoy plants by hydroponic farming is explained by variables in this research, while the remaining 1.6 percent is explained by other variables outside the research.